Optimization of PPA Unit Performance in Order to Realize Professional Legal Protection for Victims in the Polres Area of Pekalongan - Pringadhi, Bayu Pratama Putra (Police Studies Review, 2024)
The protection of women and children is very important in a country that prioritizes social justice for all its people. Pekalongan District Police, as one of Indonesia's police forces, is responsible for providing professional legal protection to victims, especially women and children. Therefore, this study aims to optimize the performance of the Women and Children Protection Service Unit at Pekalongan Police Station. The descriptive qualitative research approach was employed, with data collected through interviews, observations, and document studies. Respondents interviewed consisted of PPA unit personnel, victims, and witnesses. Data analysis was carried out qualitatively using data reduction techniques, data presentation and conclusion drawing. The results showed that the PPA Unit at Pekalongan Police still experienced several obstacles in providing professional legal protection to victims, especially in terms of human resources and facilities and infrastructure as well as in terms of coordination with relevant stakeholders. In terms of human resources, the PPA Unit still has to improve the quality of knowledge. In terms of facilities and infrastructure, it can maximize the room owned by Pekalongan Police.